The effects of Customer Relationship Management (CRM) and customer perceived value dimensions: a proposed conceptual framework for customer loyalty - Agbemabiese, George Cudjoe; Hashim, Haslinda; Jo Ho, Ann; Sambasivan, Murali (IGI Global, 2022)
The failure of customer relationship management (CRM) initiatives to improve the bottom-line has led to authors questioning the direct unconditional effects of CRM on customer loyalty, with calls for more studies to examine possible intervening variables explaining the mechanism of influence between CRM and customer loyalty. While researchers have advanced knowledge on the generative mechanisms by which CRM influences customer loyalty, the mediating role of customer perceived value (CPV) dimensions including functional, social, and emotional values have received very little attention in the literature. This chapter proposes a comprehensive model incorporating CRM, CPV dimensions (including functional, emotional, and social values), and customer loyalty. Underpinned by the resource based-view and equity theories, the proposed model explores the direct and indirect effects of CRM on customer loyalty through CPV dimensions within the banking context. The integrated framework is a result of a careful review of the literature pertaining to CRM, customer loyalty, and CPV.